The Effect of Physical Contact on Pre-slaughter Stress and Fear Reactions in Broiler Chickens - Turkyilmaz, Mehmet Kenan; Fidan, Evrim (International Journal of Poultry Science, 2006)
This study investigated the effects of regular physical contact on fear and stress reactions and some performance parameters in broiler chickens. Broiler chicks were exposed to inverted handling with an experimenter for 5 min daily (Group-I), upright handling with an experimenter for 5 min daily (Group-II) and no handling (Control) during the study (1-37 days). Tonic immobility (TI) duration and corticosterone concentration were used to measure the levels of fear and stress, respectively. Present findings indicated that physical contact of human had no significant effect on tonic immobility duration, number of induction and the level of corticosterone in broiler chickens. As a result the body weight, feed intake, feed conversion ratio and mortality was not affected by this treatment.